A mimetic finite difference method using Crank-Nicolson scheme for unsteady diffusion equation - Mannarino S., Iliana A. A. (2009)
In this article a new mimetic finite difference method to solve unsteady diffusion equation is presented. It uses Crank-Nicolson scheme to obtain time approximations and second order mimetic discretizations for gradient and divergence operators in space. The convergence of this new method is analyzed using Lax-Friedrichs equivalence theorem. This analysis is developed for one dimensional case. In addition to the analytical work, we provide experimental evidences that mimetic Crank-Nicolson scheme is better than standard finite difference because it achieves quadratic conver- gence rates, second order truncation errors and better approximations to the exact solution.